Penyelesaian Tindak Pidana Pencurian Melalui Pendekatan Restorative Justice (Studi Kasus Putusan Pengadilan Negeri Bojonegoro No.148/Pid.C/2025/Pn Bjn) - Pratiwi, Dinda Adelia; Handayani, Tri Astuti; Yasin, Bukhari (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
The Crime of Theft is an act of harm to the victim for the actions of the perpetrator in taking valuables owned by the victim. At this time, the Crime of Theft is still a fairly significant problem in terms of crime and social loss with diverse backgrounds, which are often carried out collectively by perpetrators in the form of taking the victim's belongings. Along with the development of the criminal justice system in Indonesia, the criminal justice system offers a restorative justice approach as an alternative option in resolving legal cases, which emphasizes the restoration of the conditions as they were before and the balance of interests of all parties involved. In this case, the application of restorative justice is not only applied to the Juvenile Court System, but can also be applied to Police Regulations (Investigation and Investigation), Prosecutor's Office (Prosecution) and Courts (Final Decisions). In this study, a normative juridical approach method was applied, which emphasizes analysis of applicable legal norms and principles as the main basis for the study, especially in the case of the crime of Theft. This study is intended to examine the application of the restorative justice approach in handling the crime of Theft, as reflected in the Bojonegoro District Court Decision Number 148/Pid.C/2025/PN Bjn. This approach is considered effective in producing a fairer, more effective, and recovery-oriented settlement compared to punishment alone. Therefore, it can be concluded that the results of this study show that the application of restorative justice in the settlement of theft crimes can be a relevant alternative solution in realizing a fair and humane criminal justice system.